Membrane performance and build-up of solute during small scale reverse osmosis operation - Nasir, Subriyer (Curtin University, 2007)
Reverse Osmosis (RO) is widely accepted as an alternative method to produce freshwater from different feed water sources. This technology competitively substitutes the thermal processes in the near future because of several advantages particularly in energy saving. The success of RO operation will, however, depends largely on the overall membrane performance. Deposit or build-up of solute is one of the main reasons for membrane operation failure. Build-up of solute or deposit which is known as fouling and scaling will decrease the permeate flux and increase the energy consumption in particular after prolonged operation of RO. The thesis presents the experimental results obtained in a small-scale RO system. The aim of this study is to investigate the effect of sodium chloride and calcium carbonate on the membrane performance and subsequent build-up of solute on the membrane surface. The experiments were carried out in a small-scale of RO (2 m3/day capacity) with spiral wound membrane using simulated feed water, secondary effluent, and groundwater samples. The parameters chosen for the experiments are applied pressure (1250-4750 kPa), and concentration of sodium chloride (l00-5000 mg/L) and calcium carbonate (50-100 mg/L).The results from feedwater runs indicated that initial sodium chloride and calcium carbonate in feed water and applied pressure affects the overall membrane performance. However, there is no significant effect on membrane performance for sodium chloride with concentration below 1200 mg/L and applied pressure lower than 2250 kPa. Applied pressure appears to have an impact on build-up of sodium and calcium on the membrane surface for pressures greater than 2750 kPa. For typical small-scale RO system used in this experiment, build-up of calcium will slightly decrease with given pressure caused by the characteristic of membrane that easily removes the divalent ions. The osmotic pressure of solution also strongly affects the permeate flow rate in particular for relatively higher sodium concentration (> 2500 mg/L). As a consequence of higher osmotic pressure, zero permeate flux is achieved when sodium chloride concentration was greater than 5000 mg/L and applied pressure lower than 1750 kPa. Results also indicated that fouling might pose a potential problem in small-scale RO operation. In order to investigate the membrane performance, experiments with secondary effluent samples were also performed. Results indicated that water recovery percentages and permeate flux also linearly increase with applied pressure. However, effectiveness of membrane decreases less than 98% otherwise build-up of solute tends to increase. It is suggested that lower values of the water recovery percentage (WRP) and permeate flux (Jw) are caused by the characteristic of secondary effluent that have high-suspended solids, organic carbon, and minerals. Further, the membrane performance also examined with ground water as feed water sample.Results showed that both water recovery percentage and permeate flux linearly increased with operating pressure. However, intensive pretreatment are required as a result of higher concentration of humic acid and iron in raw feed. Percentages of ion rejection for sodium and calcium are greater than 98 and 99% respectively. The high ion rejections are mainly due to the characteristics of groundwater with low TDS and EC. Sodium and calcium build-up in a small-scale RO system considered appears to be affected by the applied pressure. Build-up of solute in small-scale of RO system has been predicted using the empirical model proposed in this work. Two ions namely sodium and calcium in feed water considered as predominant ions responsible for fouling and scaling on the membrane surface. Four main parameters namely, applied pressure (P), permeate flux (Jw), membrane resistance (Rm), and feed concentration (Cf) are considered which strongly affect the overall membrane performance. The empirical correlations derived from experimental observation among these parameters can be expressed as follows: In Md NaCI = O. 77 In P + 0.67 In Jw + 0.19 In Rm + 0.171n Cf In Md CaCO3= 0.96 In P + 0.75 In Jw + 0.2 In Rm - 0.07 In CfThe empirical models proposed in this thesis may be useful for predicting the buildup of solute on the membrane surfaces. In the present work, an attempt has been made to estimate the energy consumption and unit cost for desalting of different feed water samples in a small-scale RO system. In RO plants, unit cost of water production from feed water is primarily governed by the energy required for pumping raw water. Estimates of specific energy consumption (SEC) for desalting of sodium chloride, combined sodium and calcium carbonate solutions were found to be in the range of 0.79 - 3.21 and 0.81 - 3.22 kwh/m3 respectively. For groundwater and secondary effluent, they are estimated to 0.63 - 1.71 and 0.79 - 2.02 kWh/m3 respectively. Moreover, energy consumption for different feed water samples was used to estimate the unit cost for water production. Estimation of unit costs for combined sodium chloride and calcium carbonate solution, groundwater, and secondary effluent runs are $2.06 - 3.22, $1.98 - 2.57 and $1.56- 2.66 respectively. In this work, unit cost is still higher due to greater energy consumption .by the pumping system which is required in a small-scale RO operation. Based on the experimental results, it appears that the characteristics of feed water samples affect the membrane performance and their effects must be taken into account in the design of RO units so as to reduce the unit cost for water production.The findings from the present experimental and modelling work are of practical significance in not only providing the knowledge base in the area of desalination but also paves the way for developing tools for the prediction of build-up of solutes on membrane surface in full scale reverse osmosis operations.